Experimental System and Software: Two-dimensional Return of the Platform to the Sound Source - Romanchuk, Andrii; Chyhin, Vasyl (Видавництво Львівської політехніки, 2023)
We created a system, debugged it, and conducted experimental studies of the two-dimensional rotation of the supporting platform (with a camera, and a light source.) On the source of sound waves. The system was assembled based on two SYNCO Mic-M3 cardioid condenser microphones and an Alesis IO-4 sound card. We wrote original software for analyzing and transmitting the result of processing harmonic acoustic signals for the response of the Arduino Uno control board. The rotation of the 2D platform is caused by two MG995 servos controlled by this microcontroller. We used a model of a serial COM port, which allows to send data received from the platform in the form of packets for processing by a portable personal computer. Based on the results of the experimental test and the basis of the literature data, a model of control of the two-dimensional platform of returning to the source of sound has been offered.
Keywords: two-dimensional rotation platform; software; servomotor; microcontroller; microphone